2022
DOI: 10.1007/s10143-022-01826-z
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib for recurrent high-grade glioma: a unicentric retrospective analysis of feasibility, efficacy, and toxicity

Abstract: We describe here 11 consecutive patients with recurrence of high-grade glioma treated with regorafenib at our university medical center. The majority of patients had MGMT promoter methylation (9/11 cases). Regorafenib was given as 2nd line systemic treatment in 6/11 patients and 3rd or higher line treatment in 5/11 patients. The median number of applied cycles was 2 with dosage reductions in 5/11. Response to treatment was observed in 4/11 (PR in 1/11, and SD in 3/11). Median overall survival for the cohort wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…We reported a lower rate of adverse events of any grade (69.7%) according to CTCAE v5.0 as compared with other real-life studies (90.7% -100.0%). 23,24,27 Similarly, we observed a lower rate of adverse events grade 3-4 (31.8%) compared with other series (53.0% -83.3%). 24,27,28 Furthermore, we reported a reduced incidence of some adverse events that were described as frequent complications in other studies: for example, the incidence of liver enzymes elevation was lower in our series than in REGOMA trial (15.2% vs 48.0%), as well as that of hypertension (12% vs 22%), low platelet count (10.6% vs 20.0%), hypothyroidism (12.1% vs 19.0%), or increased pancreatic enzymes (4.5% vs 20.0%); on the other hand, we reported a higher incidence of fatigue (33.3% vs 24.0%) and a similar incidence of hand-foot syndrome (27.3% vs 22.0%) as compared with REGOMA.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We reported a lower rate of adverse events of any grade (69.7%) according to CTCAE v5.0 as compared with other real-life studies (90.7% -100.0%). 23,24,27 Similarly, we observed a lower rate of adverse events grade 3-4 (31.8%) compared with other series (53.0% -83.3%). 24,27,28 Furthermore, we reported a reduced incidence of some adverse events that were described as frequent complications in other studies: for example, the incidence of liver enzymes elevation was lower in our series than in REGOMA trial (15.2% vs 48.0%), as well as that of hypertension (12% vs 22%), low platelet count (10.6% vs 20.0%), hypothyroidism (12.1% vs 19.0%), or increased pancreatic enzymes (4.5% vs 20.0%); on the other hand, we reported a higher incidence of fatigue (33.3% vs 24.0%) and a similar incidence of hand-foot syndrome (27.3% vs 22.0%) as compared with REGOMA.…”
Section: Discussionsupporting
confidence: 76%
“…12 Patients with GBM IDH-mutant were 5/54 (9.3%) in the observational real-life trial from Lombardi et al, 23 whereas other retrospective studies included more heterogeneous cohorts of patients with both GBM IDH-wildtype and lower-grade gliomas IDH-mutant. [24][25][26][27][28] In our study, we employed for the rst time a dose escalation protocol to improve patient tolerability and compliance. We reported a lower rate of adverse events of any grade (69.7%) according to CTCAE v5.0 as compared with other real-life studies (90.7% -100.0%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the OS of patients treated with lomustine from REGOMA trial was remarkably short (5.6 months) as compared with that of patients included in the lomustine single arms of other randomized controlled trials (median OS 7.1-10.4 months [5,72,73], which could imply an overestimation of regorafenib efficacy. Few other studies have shown similar impact on survival [74][75][76][77][78][79], but a higher rate of adverse events than in REGOMA, thus raising concerns over tolerability. A lower intensity regimen proved as effective as the standard 160 mg daily schedule used in REGOMA trial (median PFS and median OS of 2.0 months and 7.4 months), but with lower adverse events [80].…”
Section: Clinical Trials Of Antiangiogenic Tyrosine Kinase Inhibitors...mentioning
confidence: 96%